Histomorphological and Histochemical Studies on Larynx of Pigs - Parkash, Tej (Indian Journal of Veterinary Anatomy, 2020)
Six heads of young pigs of 8-10 months age, of local mixed breed pigs were used to study the histology and histochemistry of the larynx. Larynx was comprised of epiglottis, paired arytenoid, thyroid and cricoid cartilages. Histologically the epiglottis, inter-arytenoid, arytenoid cartilages and vocal cords were lined by stratified squamous non-keratinized epithelium with lymphoid follicles, fatty tissue, sero-mucous glands, and serous demilunes in the propia submucosa of epiglottis, inter-arytenoid and arytenoid cartilages. The thyroid and cricoid cartilages were lined by pseudostratified columnar ciliated epithelium with PAS positive goblet cells. Lymphoid follicles, mucous glands and fine blood capillaries were observed in the propria submucosa. Predominantly, mucous glands present in the propria submucosa were strongly positive for histochemical studies.